Assessing the impact of daylight exposure on sleep quality of people over 65 years old. (March 2020) - Flores-Villa, Lorna; Unwin, Jemima; Raynham, Peter
Due to our social behaviours, people spend at least 80% of their time indoors, mostly under artificial light. In research and building design, daylight is considered a valuable asset because it is the primary source of free, good quality light and it is suggested that it has a positive influence on human performance, health and sleep quality. There is a tendency in the population for increasingly poor sleep quality with age, and this affects at least 50% of the elderly population. Research on sleep disruption has found that especially in the elderly population, interrupted sleep can affect alertness, cognitive performance and mood. This increases the risk of falls, increases fatigue and reduces some other mental functions. Exposure to daylight (indoors and outdoors) is expected to reduce sleep disruption. Physical activities and sleep quality were assessed using 32 participants living independently in the UK, aged between 65 and 95 years old. The study was divided into two seasons due to a considerable difference in daylight availability in summer and winter. In each season participants completed the Pittsburgh Sleep Quality Index (PSQI) questionnaire, Morningness–Eveningness Questionnaire (MEQ) and a seven-day sleep diary/log activity; where time spent outdoors was identified. It was expected that participants who reported less exposure to daylight during summer and winter would report worse sleep quality. However, this was not the case; subjective sleep quality did not differ greatly between summer and winter, even though exposure to daylight varies greatly between seasons. This study explores the relationship between exposure to daylight throughout two different seasons and people's chronotypes, physical activities and sleep quality (between and within participants). This information is essential to find means of supporting an ageing population. Practical applications : In the built environment, daylight is an important feature to consider for the occupant's health and wellbeing. This research provides real-world insight into the amount of daylight that active aged people are exposed to during two seasons in London, and how this could impact their overall sleep quality. The findings suggest that exposure to daylight could benefit people over 65 years old with poor sleep quality by reducing the number of awakenings during the night. This research provides a step towards understanding how daylight exposure effects people, and can be used to inform housing design for the ageing population.